Investigation On Safety Culture And Awareness Among Construction Workers At Height For Accident Prevention - Ilham Nafiz, Mohamad Raymee (2025)
This study aims to assess the safety culture and awareness among workers performing tasks at height in construction sites and to identify individual, organizational, and management factors influencing workplace safety. Additionally, the study seeks to develop an intervention plan to enhance safety practices and prevent accidents. Using a quantitative approach, 36 construction workers participated in a survey questionnaire, the data were analyzed using SPSS, incorporating correlation analysis, Spearman’s correlation coefficient, ANOVA, and normality tests such as histograms, Q-Q plots, detrended Q-Q plots, and box plots. These statistical methods were utilized to examine relationships between variables, assess differences in safety awareness levels, and determine significant influencing factors. Recommendations include increasing the frequency of safety training sessions, allocating sufficient resources for safety initiatives, and encouraging open communication regarding safety concerns. This research contributes to efforts aimed at reducing workplace accidents and creating safer construction environments.